Are seedlings diagnostic in Neotropical Entada (Leguminosae)? Seedling morphology supports the reinstatement of Entada polyphylla - Rodrigues, Rodrigo Schütz (Phytotaxa, 2015)
Entada (Leguminosae) is a pantropical genus encompassing four Neotropical species, E. gigas (E. sect. Entada), E. polyphylla, E. polystachya and E. simplicata (E. sect. Entadopsis). However, the taxonomic status of E. polyphylla is still disputed, being treated as a separate species or a variety of E. polystachya. This article aims to take a comprehensive view of seedlings of Neotropical Entada, addressing the question of whether seedling morphology provide diagnostic characters that support the recognition of E. polyphylla at the species level. Seedlings of E. polyphylla were described and illustrated, whilst seedling data for the remaining Neotropical species were based on the literature. Entada polyphylla has an exclusive set of seedling characters within E. sect. Entadopsis, including cryptocotylar, hypogeal, reserve seedlings, long cotyledonary petioles, short cotyledon lobes, cataphylls and alternate, bipinnate eophylls. Therefore, seedling morphology supports the recognition of E. polyphylla as a distinct species and its reinstatement is here proposed. In addition, each of the four New World species of Entada can be diagnosed by their seedlings, and an identification key is also provided.